Model and Method for Evaluation and Forecast of the Changes of Visual System Functional State in Consequence of Visual Work - Kochina, M.L.; Kozak, L.M.; Yavorsky, O.V.; Firsov, O.G.; Yevtushenko, A.S. (Cybernetics and computer engineering, 2020)
The purpose of the paper is to develop a method for evaluating and predicting the operators` functional state based on a model for predicting changes of the VS state under the visual work, as well as to implement this method in clinical decision support system for analyze /the SV states changes because of visual work. Метою роботи є розроблення методу оцінювання та прогнозування функціонального стану операторів на основі моделі прогнозування змін стану зорової системи за умов зорової праці, а також реалізації методу в автоматизованій системі підтримки прийняття рішень лікарем для аналізу стану ЗС оператора внаслідок зорової праці Построена модель прогнозирования изменений состояния зрительной системы вследствие зрительной работы, которая базируется на комплексе показателей функционального состояния зрительной системы с использованием алгоритма нечеткой кластеризации (c-средних) и системы нечеткого вывода Сугено. По результатам предыдущих исследований и построенной прогнозной модели разработан метод оценки и прогнозирования функционального состояния человека и его зрительной системы